The efficacy and safety of thalidomide-based therapy in patients with advanced non-small cell lung cancer: a meta-analysis - Liu, Ying; He, Shuhua; Ding, Yi; Huang, Jing; Zhang, Yuqing; Chen, Longhua (Contemporary Oncology/Współczesna Onkologia, 2014)
Several randomized controlled clinical trials have compared therapy with or without thalidomide in the treatment of advanced non-small cell lung cancer (NSCLC). However, these studies did not produce consistent results. We carried out a meta-analysis to determine the efficacy and safety of thalidomide-based therapy in patients with advanced NSCLC. For this meta-analysis, we selected randomized clinical trials that compared thalidomide in combination with other therapy or other therapy alone in patients with advanced NSCLC. The outcomes included median overall survival (OS), one- and two-year survival, tumor response, and toxicities. Hazard ratios (HRs) or risk ratios (RRs) were reported with 95% confidence intervals (CIs). A total of 5 eligible trials were included for the meta-analysis, with 729 patients in the thalidomide group and 711 patients in the control group. Compared with non-thalidomide-based therapy, patients receiving thalidomide plus other therapy did not differ significantly in terms of one- and two-year survival or tumor response (RR = 1.32, 95% CI: 0.66–2.63, p = 0.43; RR = 1.22, 95% CI: 0.48–3.11, p = 0.68; RR = 1.05, 95% CI: 0.92–1.19, p = 0.51, respectively). However, thalidomide-based therapy induced more grade 3–4 dizziness and constipation (RR = 2.05, 95% CI: 1.10–3.81, p = 0.02; RR = 4.78, 95% CI: 1.84–12.38, p = 0.001, respectively). The addition of thalidomide to other therapy did not improve survival and tumor response in patients with advanced NSCLC, and thalidomide-based therapy was associated with more grade 3/4 dizziness and constipation.